Factors that influence employee’s purchase intention towards celebrity endorsement in health and beauty industry / Wan Farah Nadia Wan Iskandar - Wan Iskandar, Wan Farah Nadia (Faculty of Business and Management, 2018)
The purpose of study is to identify factors that influence employee’s purchase intention towards celebrity endorsement in health and beauty industry. A review of the study in each area identifies key findings, collecting results and problem statement. This research will review’s the celebrity endorsement literature review with a focus on the factors that influence employee’s intention. There are attractiveness, trustworthiness and attitude that control employee’s independent variable and employee’s purchase intention towards celebrity endorsement in health and beauty industry dependent variables. The researcher has adopted Theory of Planned Behaviour. The problems that had been studying when consumer refers to the false information, emotional effects, endorsed multiple products for money and big spender. This research will be supported by a sample size of minimum 103 employees from the total population of 140 employees of Jati Force Sdn Bhd. Data will be collected by distributing questionnaire to employees and the researchers will use non-probability sampling method.